Experimental Study on the Dynamic Performance of a New High-Speed Spindle Supported by Water-Lubricated Hybrid Bearings - Lin Wang; Hua Xu (Shock and Vibration)
The dynamic performance of a new high-speed spindle supported by water-lubricated hybrid bearings is experimentally studied on a test rig. The present design allows the speed of the spindle up to 30,000 rpm, with a bearing internal diameter of 40 mm, which makes it possible to simulate many actual machining processes. Some experiments have been presented to study the mechanical and thermal behaviors of the spindle and its supporting hybrid bearings. The maximum temperature rise is less than 15°C with a speed of 30,000 rpm and a water supply pressure of 2.5 MPa. The spindle radial run-out of the rotational frequency is about 1 µm. Stability of the spindle system has been improved. The experimental results indicate that water-lubricated hybrid bearings are valuable choices to replace ceramic bearings and air bearings as support for spindles under high-speed, high-precision, and heavy-load machining conditions.